ANALISIS PENGARUH SISTEM REWARD, MOTIVASI KERJA, DAN KOMITMEN ORGANISASIONAL TERHADAP RETENSI KARYAWAN (Studi Pada Karyawan PT Primayudha Mandirijaya) - Permata, Parenda Rizkya; Rahardja, Edy (Diponegoro Journal of Management, 2016)
Employees are the most important part of the company. Therefore, the company should be able to treat employees properly. However, with the phenomenon of the high turnover in PT Primayudha Mandirijaya indicate that efforts are being made to ensure that the employees remain in the company is still less than the maximum. This study used three independent variabels are the reward system, employee motivation, and organizational commitment with one dependent variabel is employee retention. This study aims to examine and analyze the effect of reward systems, employee motivation, and organizational commitment to employee retention in PT Primayudha Mandirijaya.            Data collection methods used in this study was a questionnaire by using random sampling method. The sample used in this study were jobholder of PT Primayudha Mandirijaya with the number of 83 respondents. This study uses data analysis includes reliability test, validity test, classic assumption test, multiple linear regression analysis, coefficient determination. F test and t test.            The result of this study indicate that variable reward system, employee motivation, and organizational commitment positively influence on the employee retention of PT Primayudha Mandirijaya. These variabels give a contribution of 52.8% of employee retention. The remaining 47.2% is influenced by variables outside of this study.